Ninoy at Cory Magkabiyak na Bayani - Landicho, Domingo G., 1939- (Quezon City C & E Publishing, 2010)
The life stories of Senator Benigno S. Aquino Jr. and President Corazon C. Aquino as part of the Philippine political history.
College Students
In Tagalog.